A new carboxyl-functionalized P3HT/TiO2 composite photocatalyst: preparation, structure and prompted activity through interfacial engineering. (2017) - Zhang, Jianling; Yao, Yan; Yang, Haigang; Yu, Yuyan; Xu, Shoubin; Dan, Yi
No abstract available